2013
DOI: 10.1016/j.jvs.2013.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of fetal radiation exposure during pregnancy

Abstract: Lack of knowledge of fetal radiation exposure has concerned many vascular surgeons, prompting them to wear double lead aprons during pregnancy, and perhaps prevented numerous other women from entering the field. Our study showed negligible radiation exposure on fetal monitoring suggesting that with the appropriate safety precautions, these concerns may be unwarranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Digital subtraction angiography (DSA) is currently used more often than computed tomography (CT) in the diagnosis of intracranial aneurysms, as well as during the embolization procedure; however, DSA is known to deliver higher doses of radiation (29). Nonetheless, it has been reported that the amount of radiation delivered during these situations is negligible (5,39). Fetal shielding, excluding fluoroscopy near the uterus, and safer technologies have been used successfully to combat radiation damage (26).…”
Section: Methods Of Aneurysm Treatmentmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) is currently used more often than computed tomography (CT) in the diagnosis of intracranial aneurysms, as well as during the embolization procedure; however, DSA is known to deliver higher doses of radiation (29). Nonetheless, it has been reported that the amount of radiation delivered during these situations is negligible (5,39). Fetal shielding, excluding fluoroscopy near the uterus, and safer technologies have been used successfully to combat radiation damage (26).…”
Section: Methods Of Aneurysm Treatmentmentioning
confidence: 99%
“…However, radiation exposure for pregnant women must conform to an even higher level of precaution [10, 12-15]. There are few female ocular oncologists who perform plaque brachytherapy regularly in North America; therefore, we aimed to evaluate their practice trends, overall level of exposure, and consequent concern.…”
Section: Discussionmentioning
confidence: 99%
“…A few smaller studies have considered the specific radiation exposure to the foetus by wearing a dosimeter on the abdomen beneath a lead apron during screening procedures, all of which have failed to show exposure levels greater than the 1 mSv limit. One prospective study of 32 pregnant vascular trainees showed negligible radiation exposure to the foetus . A recent article showed higher radiation doses in the home environment than during a screening list, although this study included just one pregnant urologist .…”
Section: Screening and Radiationmentioning
confidence: 98%